INTERNALISASI AMALAN-AMALAN TAREKAT NAQSYABANDIYAH DALAM MEMPERKUAT KEIMANAN (Studi Kasus di Desa Upang Ceria Kecamatan Muara Telang Kabupaten Banyuasin) - Nike Suryani; Idrus Alkaf; Ahmad Soleh Sakni (JIA (Jurnal Ilmu Agama), 2022)
The Tarekat in Upang Ceria Village has something interesting, namely from its inclusive nature, inclusiveness can be seen from the teachings and daily behavior of the followers of the Naqsyabandiyah Tarekat, many good changes have occurred after following this tarekat, both in the personal and social fields. The purpose of this study was to find out about how the community internalizes the practices of the Naqsyabandiyah Order in strengthening faith and to find out how the behavior of the followers of the Naqsyabandiyah Tarekat is. This research is a qualitative research in the form of field research. The data sources in this study are primary data from observations and interviews with followers of the Naqsyabandiyah Order, and secondary data includes documentation related to research. The data was collected by documenting the results of observations and interviews conducted in Upang Ceria Village as well as from various other references. The data analysis technique is carried out by data reduction, data presentation, and drawing conclusions about the results of the study. The results of the study were found in the internalization of the practices of the Naqsyabandiyah Order using two ways, namely individual guidance (Fardiyyah) which was done by means of allegiance, then self-accustoming , then do remembrance individually, and perform the practices of the Naqsyabandiyah Order. Furthermore, there is collective guidance, namely through tawajjuh and suluk activities. Based on the results of observations and interviews on the behavior of the followers of the Naqsyabandiyah Order in Upang Ceria Village, there have been many changes in lifestyle and behavior that have begun to gradually become better in order to get closer to Allah.